2017
DOI: 10.7287/peerj.preprints.3099
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tolerance: the forgotten child of plant resistance

Abstract: Plant resistance against insect herbivory has greatly focused on antibiosis, whereby the plant has a deleterious effect on the herbivore, and antixenosis, whereby the plant is able to direct the herbivore away from it. Although these two types of resistance may reduce injury and yield loss, they can produce selection pressures on insect herbivores that lead to resistance. Tolerance, on the other hand, is a more sustainable pest management strategy because it involves only a plant response and therefore does no… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Mechanisms of tolerance are generally poorly understood (Koch et al, ; Peterson et al, ). It has been suggested that compensation for damage caused by herbivory or pathogen infection could consist of several factors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Mechanisms of tolerance are generally poorly understood (Koch et al, ; Peterson et al, ). It has been suggested that compensation for damage caused by herbivory or pathogen infection could consist of several factors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that compensation for damage caused by herbivory or pathogen infection could consist of several factors. These include increased chlorophyll concentrations, increased nutrient uptake, increased use of stored resources, delayed flowering and senescence, increased size or number of tissues such as leaves, modified phytohormone balance and altered resource allocation patterns between roots and shoots, or between growth and reproduction (Koch et al, ; Mitchell et al, ; Pagán & García‐Arenal, ; Peterson et al, ; Strauss & Agrawal, ; Tiffin, ). In S. nigrum , herbivory was shown to lead to down‐regulation of the hormone system and a subsequent increase in root allocation, which may favor competition with other plants following herbivory (Schmidt & Baldwin, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations